Overall, specific, and metastasis‐free survival of Afro‐Caribbean men with pathological Gleason 6 prostate cancer. Issue 4 (23rd December 2019) - Mollard, Philippe; Perrot, Emmanuel; Blanchet, Pascal; Brureau, Laurent
Abstract: Background: Several studies in the Caucasian population have shown that patients with Gleason 6 prostate cancer, based on surgical specimens, have low or no risk of metastasis. However, there is no data for men of African ancestry. The objective of this study was to estimate the overall, specific, and metastasis‐free survival (MFS) of patients with a Gleason 6 score, based on the surgical specimen. Patients and Methods: This was a monocentric retrospective study that included 723 consecutive patients treated by radical prostatectomy between 1 January 1 2000 and 31 March 2018, with a Gleason score of 6 based on the surgical specimen. Specific survival (SS) was defined as the time elapsed between surgery and death attributed to prostate cancer. Overall survival was defined as the time elapsed between surgery and death from all causes. The causes of death were verified in the medical records. Survival analyses without biochemical recurrence (BCR) and without salvage treatment were performed according to the Kaplan–Meier method. The Cox model was used for univariate and multivariate analyses. Results: In total, 691 patients were included because 32 were excluded for missing data. Overall 5‐ and 10‐year survival was 94.2% and 87.1%, respectively. SS and MFS were 100%, with a median follow‐up of 8.5 years. The BCR rate was 16.5%, with a median time to BCR of 5.1 years. The frequency of salvage treatment was 13.0%, with a median time to surgery of 7.3 years. In univariate analysis, PSA, pathological stage, seminal vesicle invasion, positive margins, and lymph node dissection were significantly associated with an increased risk of BCR and salvage treatment, but only PSA and positive margins were significantly associated by multivariate analysis. Discussion/Conclusion: No metastasis or disease‐specific deaths were observed for men with Gleason score ≤6 prostate cancer at radical prostatectomy, in particular, men of African ancestry.